Optimalisasi Penggunaan E Commerce untuk Mempeluas Pangsa Pasar pada UMKM Makanan Olahan - Ali Imron; M. Iqbal Notoatmojo; Rizka Ariyanti (Jurnal Ragam Pengabdian, 2025)
This community service program aims to enhance the capacity of micro, small, and medium enterprises (MSMEs) in the processed food sector in Pekalongan Regency to utilize e-commerce as a strategy to expand their market reach. The main issues identified include low digital literacy and suboptimal use of digital platforms for product marketing. Through an action-based learning approach, the program was implemented through structured training and mentoring activities focused on social media utilization, marketplace registration, and the creation of digital promotional content. The results indicate an improvement in participants’ skills in managing social media accounts, registering on marketplaces, and producing engaging promotional materials. The long-term outcomes of the program include increased sales volume, higher income, and sustainable digital business practices among MSMEs. Additionally, the program produced scientific publications, video documentation, and a replicable training module. This community service initiative contributes to strengthening the competitiveness of MSMEs in the digital economy era.